Using ‘appreciative inquiry’ in India to improve infection control practices in maternity care: a qualitative study - Sharma, Bharati (Glob Health Action, 2015)
BACKGROUND: Infections acquired during childbirth are a common cause of maternal and perinatal mortality and morbidity. Changing provider behaviour and organisational settings within the health system is key to reducing the spread of infection. OBJECTIVE: To explore the opinions of health personnel on health system factors related to infection control and their perceptions of change in a sample of hospital maternity units. DESIGN: An organisational change process called ‘appreciative inquiry’ (AI) was introduced in three maternity units of hospitals in Gujarat, India. AI is a change process that builds on recognition of positive actions, behaviours, and attitudes. In-depth interviews were conducted with health personnel to elicit information on the environment within which they work, including physical and organisational factors, motivation, awareness, practices, perceptions of their role, and other health system factors related to infection control activities. Data were obtained from three hospitals which implemented AI and another three not involved in the intervention. RESULTS: Challenges which emerged included management processes (e.g. decision-making and problem-solving modalities), human resource shortages, and physical infrastructure (e.g. space, water, and electricity supplies). AI was perceived as having a positive influence on infection control practices. Respondents also said that management processes improved although some hospitals had already undergone an accreditation process which could have influenced the changes described. Participants reported that team relationships had been strengthened due to AI. CONCLUSION: Technical knowledge is often emphasised in health care settings and less attention is paid to factors such as team relationships, leadership, and problem solving. AI can contribute to improving infection control by catalysing and creating forums for team building, shared decision making and problem solving in an enabling environment.